THE IMPORTANCE OF HUMAN RESOURCE MANAGEMENT FOR SMALL AND MEDIUM ENTERPRISES - Marlinda Syafira; Irfan Hakim; Eza Azmy Fadlurrahman; Imas Eka Prastiti; Cantika Nurhaliza (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This study qualitatively explores the influence of human resource management (HRM) on the performance of Micro, Small, and Medium Enterprises (MSMEs). Case studies were conducted on several MSMEs in [research locations] using in-depth interview methods and document analysis. The results shows that HRM practices, such as proper employee selection, continuous training, and an effective performance evaluation system, contribute significantly to improving the performance of MSMEs. In addition, this study also found that there was a positive relationship between employee job satisfaction and MSME performance